THE USE OF VETERINARY MACROSCOPIC ANATOMY AS AN EDUCATIONAL INSTRUMENT IN ELEMENTARY AND HIGH SCHOOL IN BRAZIL (Environmental Smoke, 2022)
This paper deals with veterinary macroscopic anatomy as an educational tool in elementary and high school in Brazil and the way it is taught in Brazilian public schools. The main objective is to know the development of macroscopic teaching in basic education, in order to demonstrate the relevance of knowing the anatomy of animals in practice. It is known that the teaching of both human and animal anatomy is linked to the teaching of the biological sciences, however, we realize that the teaching / learning of these students have been insufficient, as they present practical classes associated with the lack of interest of macroscopic anatomy, and there is also a certain indifference on the part of teachers and the institution itself to provide resources that lead teachers to bring knowledge from theory to practice. This study is evidenced by the qualitative character, removing from the objective of the research the answer to the above problematizing question.